Effects of Ephedras Herba on the activity of antioxidant - Seong-Min Song; Hyung-Ho Lim; Yun-Kyung Song; Ki-Rok Kwon; Tae-Jin Lim (Korean Pharmacopuncture Institute, 2007)
Objectives : The purpose of this study was to investigate the antioxidative effects of Ephedrae Herba extract. Methods : Total antioxidant status was examined by total antioxidant capacity(TAC), total antioxidant response(TAR) against potent free radical reactions, total phenolic content, DPPH radical scavenging activities, and the inhibitory effect of the extract on lipid peroxidation in rat liver mitochondria. Results : 1. TAC and TAR of Ephedrae Herba extract at the concentration of 5mg/ml were 3.76 and 1.65 mM Trolox equivalents , respectively. 2. Total phenolic content of Ephedrae Herba extract at the concenuation of 5mg/ml was 3.52 mM gallic acid equivalent. 3. Concentration of Ephedrae Herba extract at which DPPH radical scavenging activity was inhibited by 50% was 0.46mg/ml as compared to 100% by pyrogallol solution as a reference. 4. Ephedrae Herba extract at the concentration of 2mg/ml significantly decreased TBARS concentration by 97%, showing that Ephedrae Herba extract prevented lipid peroxidation at the low concentration. Conclusion : Thus antioxidant effects of Ephedrae Herba extract appear to be due to, at least in part, the prevention from free radicalsinduced oxidation, followed by inhibition of lipid peroxidation